CRITICAL THEORY OF THE RADICAL LOVE - Lena de Botton; Esther Oliver (Ediciones Universidad de Salamanca, 2009)
The understanding of the sexual-affective relationships has historically not been tackled by science, but placed in the context of instincts and irrationality. In this sense, the critical theory of the Radical Love provides a contribution to critical pedagogy allowing people to understand the mechanisms that direct their emotions and the process of election in the sexual-affective relationships. It is about understanding who do we fall in love for, why and to which values is this desire linked being able to have a great repercussion in our lives as it provides us with the tools to develop satisfactory sexual-affective relationships. It also offers us guidelines for a preventive education regarding gender violence by enabling us to understand the attraction models in which we have been socialised and which are influencing our desire and elections.